Persepsi Masyarakat Terhadap Penambangan Batu Kapur - Wa Ode Helma; La Ode Amaluddin; Andrias (Jurnal Penelitian Pendidikan Geografi, 2023)
The territory of Indonesia has 0.08% of the land area of the karst landscape. This has the potential to improve people's welfare. This study aims to: 1) describe the condition of limestone in Oengkolaki Village; and 2) describe the community's perception of the limestone mining of Oengkolaki Village. The method used in this research is descriptive qualitative method. The results of this study indicate that: 1) limestone mining has been carried out several years ago where mining activities can help the community's economy and can create jobs that can improve people's welfare directly by the people around the mining area; and 2) the community's perception of limestone mining gave a positive response which could be seen from the majority of community responses stating that this limestone mining activity affected the activities of the Oengkolaki Village community.